1997
DOI: 10.1084/jem.185.4.755
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Expansion of Hematopoietic Progenitor Cells in Interleukin (IL)-6–sIL-6R Double Transgenic Mice

Abstract: Soluble cytokine receptors modulate the activity of their cognate ligands. Interleukin (IL)-6 in association with the soluble IL-6 receptor (sIL-6R) can activate cells expressing the gp130 signal transducer lacking the specific IL-6R. To investigate the function of the IL-6–sIL-6R complex in vivo and to discriminate the function of the IL-6–sIL-6R complex from the function of IL-6 alone, we have established a transgenic mouse model. Double-transgenic mice coexpressing IL-6 and sIL-6R were generated and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
114
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 55 publications
5
114
1
Order By: Relevance
“…47 Evidence that IL-6 complexed to the soluble IL-6R, but not IL-6 alone, may be able to stimulate early murine progenitors, comes from phenotypic analyses of mice single transgenic for either IL-6 or sIL-6R or double transgenic for both IL-6 and sIL-6R. 34,39,40 Interestingly, double transgenic mice developed a marked extramedullary hematopoiesis in the spleen and to a lesser extent the liver while the bone marrow cellularity was not significantly changed. The liver showed distinct foci with predominantly granulopoietic cells, while large numbers of erythrocytes, granulocytes and megakaryocytes were found equally distributed in the spleen.…”
Section: Sca1mentioning
confidence: 99%
See 1 more Smart Citation
“…47 Evidence that IL-6 complexed to the soluble IL-6R, but not IL-6 alone, may be able to stimulate early murine progenitors, comes from phenotypic analyses of mice single transgenic for either IL-6 or sIL-6R or double transgenic for both IL-6 and sIL-6R. 34,39,40 Interestingly, double transgenic mice developed a marked extramedullary hematopoiesis in the spleen and to a lesser extent the liver while the bone marrow cellularity was not significantly changed. The liver showed distinct foci with predominantly granulopoietic cells, while large numbers of erythrocytes, granulocytes and megakaryocytes were found equally distributed in the spleen.…”
Section: Sca1mentioning
confidence: 99%
“…It has been hypothesized that the IL-6/sIL-6R complex is able to expand primitive resident stem cells in these primary hematopoietic organs in vivo. 34,39,40 An important objective of the present study was to investigate the potential benefit of the new designer recombinant IL-6 and sIL-6R fusion protein, H-IL-6, for the ex vivo expansion of hematopoietic UCB progenitors. Using stroma-free and stroma-supported long-term cultures, we compared several cytokine combinations in the presence or absence of this chimeric protein or with IL-6 and estimated the progenitor output by multiparameter FACS analyses and CAFC (cobblestone area forming cell) assays.…”
mentioning
confidence: 99%
“…Double transgenic mice, overexpressing both sIL-6 receptor and IL-6, are smaller than their wild type littermates and have reduced body weight. These animals have markedly reduced fat depots, enlarged spleen, and shrunken disfigured livers, suggesting a role for IL-6 in cell growth (30). Furthermore, a recent study showed that mice completely lacking IL-6 became obese and that intracerobroventricular injection of IL-6 increased energy expenditure (31).…”
mentioning
confidence: 99%
“…Furthermore, it was shown that the sIL-6-R strongly sensitizes IL-6-responsive target cells (59). transsignaling cell types that are exclusively responsive to IL-6/IL-6-R but not to IL-6 alone include hematopoietic progenitor cells (61), endothelial cells (67), osteoclasts (77), smooth muscle cells (32), and neuronal cells (39,40).…”
mentioning
confidence: 99%